PENINGKATAN PELAKU BISNIS MAHASISWA MENGGUNAKAN INVESTASI PASAR MODAL SYARIAH - Husnul Hotimah; Istika Ratna; Duwi Mega Utami; Jihan Fahira; Budiandru Budiandru (Bajang Institute, 2023)
The purpose of this study is to determine students' interest in utilizing Islamic capital market investments at this time. The focus of this research is sharia investment. A developing country that wants to carry out development must face one of the big challenges, namely the problem of unemployment. The problem of unemployment occurs because there is too much of the labor force compared to the existing jobs. To expand the income network, you have to start a business and capital. Capital is one of the considerations for students to start a business or develop a business. In conclusion, from the increase in student business people using Islamic capital market investments, it was stated that students or respondents had a high enough interest to start their businesses and one of them was by using Islamic capital market investments which were a solution to make it easier for students to get capital in an easy and lawful way.